Online News Sharing in the Face of Mixed Audiences: Context Collapse, Homophily, and Types of Social Media. Issue 5 (1st December 2020) - Kim, Eun-Mee; Ihm, Jennifer
ABSTRACT: Extending the focus on the potential for context collapse in news diffusion to diverse audiences, we investigated whether and how news sharers took account of audience characteristics to reach audiences from diverse contexts, interacted only with similar others, or remained silent (to avoid social risks). Results from surveys of 395 individuals suggest that depending on the symmetricity of social media environments, different types of similarity between news sharers and their audience increased news sharing in different ways, but the extent of context collapse did not. Implications for news sharing with similar social media audiences are discussed.